Anuson Walter Vella - Renard, Ronald D. (Ronald Duane).; Vella, Walter F. (Walter Francis) 1924-1980. Selections; Mahawitthayalai Phayap. Walter F. Vella Fund.; University of Hawaii at Manoa. Center for Asian and Pacific Studies (Chiang Mai, Thailand Walter F. Vella Fund, Payap University, 1986)
Cremation volume for Vella, Walter F. (Walter Francis), 1924-1980, American author on Thailand; comprises condolences and papers on Thailand by both crematee and others.
Keywords: Thailand -- History